IMPROVING STUDENTS' SPEAKING SKILL USING INFORMATION GAP AT SECOND YEAR OF SMP N I NGRAMPAL SRAGEN IN 2010/2011 ACADEMIC YEAR - HANDAYANI , DWI (2011)
This research aims at knowing (1) the implementation of Information Gap technique in teaching speaking, and (2) describing the students' response on Information Gap technique in teaching speaking. This research was implemented in SMP N I Ngrampal Sragen at the second year (8D), using action research. The methods of collecting the data are observation, interview, test, and documentation. The researcher taught speaking English using information gap technique. To analyze the data the researcher compared the results of pre-test and post-tests using descriptive comparative and critic analysis technique. The result of the research using information gap shows that the research consists of three cycles with each cycle consisting of four elements. By implementing information gap technique in teaching speaking, the students become active and cooperative in learning speaking. The students' motivation to speak, to practice speaking, and the students' achievement of speaking is improved. It can be seen from the result of the students' activities during the action, and the students' speaking achievement of speaking. The mean of pre-test is 64.94 (fair), and post-test is 85.76 and the improvement result of the implementation is 20.82%. Most of the students said that they love this technique. They could easily learn English speaking. The students' confidence and bravery was improved. The students admitted that their speaking was improved. The students could do the post-test better than pre-test. To concludes the teaching speaking using information gap is successful to improve the students' speaking skill.